Characterization of Spent Coffee Grounds in the Community as Supporting Materials for Renewable Energy - Muslimah Susilayati; Putut Marwoto; Sigit Priatmoko (Jurnal Penelitian Pendidikan IPA, 2022)
Coffee grounds are a by-product of the coffee brewing process. Currently, coffee grounds in the community are still untapped waste. Whereas spent coffee grounds has the potential to be converted into various high value bio-products that are environmentally friendly. This study aims to characterize coffee grounds waste which is popular in the community as a supporting material for renewable energy. This study uses a comparative method of 3 samples of Arabica coffee grounds (SCG-A), Robusta (SCG-R), and the Arabica-Robusta blend (SCG-AR) from coffee brands that are popular in Indonesian. Quantitative analysis was carried out by comparing the percentage of residual yield of the three samples. Qualitative characterization of coffee grounds was carried out using the FTIR 8300/8700 Spectrophotometer. The results of the three samples showed different rendemen values, namely 70% SCG-A, 60% SCG-R, and 80% SCG-AR. The FTIR test results showed that the three spent coffee grounds had the same functional group characteristics in the frequency range of 650â€“3900 cm-1. The detection of the hydroxyl functional group (-OH), the asymmetric strain of the CH bond of the methyl group (-CH3), and the stretching vibration of CO in the COH bond found in coffee grounds waste shows its potential as a supporting material for renewable energy if a further process is carried out in the form of pyrolysis/calcination at room temperature. 700â—¦C. Utilization of spent coffee grounds in the community can be done by establishing a Spent Coffee Grounds Bank (SCG Bank), educating the public so that they are willing to donate spent coffee grounds, and managing SCG as a supporting material for renewable energy.